A Leveraging Tacit Knowledge for Strategic Marketing Development and Decision Making in a Dynamic Business Environment: A Review - Sofia Yustiani Suryandari (Cita konsultindo, 2024)
This article examines the pivotal function of tacit knowledge in marketing and organizational decision-making within evolving business contexts. Tacit knowledge, which is often personal and challenging to articulate, serves as a strategic resource that enables organizations to comprehend unstated customer preferences, behaviors, and needs, thereby creating a competitive advantage. The integration of tacit knowledge into marketing strategies is crucial for organizations to respond effectively to market changes and meet customer expectations. The development of effective marketing strategies is increasingly reliant on the intuition and experience of leadership teams, which are supported by marketing analysis and strategic tools. In complex and rapidly changing business settings, a holistic and intuitive managerial approach is crucial for strategic decision-making, particularly under uncertainty. However, transferring tacit knowledge among team members poses challenges, such as a lack of trust and poor interpersonal relationships. These issues can be addressed by fostering strong communication and a culture of knowledge sharing within organizations. While technology can aid in the transfer of tacit knowledge through knowledge management systems and collaborative platforms, it must be complemented by efforts to build trust among individuals.